Agama dan Multikulturalisme: Belajar dari Pengalaman Australia - M. Amin Nurdin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2002)
For more than three decades, immigrants from Asia, Africa, and Latin America have settled in liberal democratic countries in Europe and North America, raising questions about cultural differences and the integration of these communities into dominant cultural and political systems. Australia, as a liberal democracy and an immigrant nation, has also faced challenges in managing religious and ethnic diversity. This paper explores the relationship between religion and multiculturalism in Australia, examining government policies on social integration and cultural preservation for immigrant communities. With a particular focus on the Muslim minority—comprising over 300,000 individuals from 67 countries—this study analyzes Australia’s response to diversity through the ideologies of assimilation and multiculturalism. By learning from Australia's experience, this paper offers insights into the broader discourse on multiculturalism, identity, and religious pluralism in democratic societies.